(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This article examines environmental problems, which are considered one of the major global challenges facing modern society, and analyzes their negative impact on human health. It highlights that society itself plays an active role in the emergence and intensification of these problems. The continuous growth of the population, along with the increasing demand for resources, places excessive pressure on the environment, leading to serious ecological challenges that directly affect human well-being.